The impact of shariah compliance on the financial performance of Malaysian Islamic banks: Moderating effect of Shariah Committee - Muhammad Ahmar, Ali (2023)
The positioning of Islamic banks as economic or social entities has been prominently debated on a global scale as Islamic bank social practices are still being neglected following their current emphasis on financial performance. Hence, this study investigates the relationship between Shariah compliance and the financial performance of Malaysian Islamic banks, as well as the moderating effect of the effectiveness of the Shariah Committee. Six Shariah compliance indicators represent the independent variables of the study. Meanwhile, the study's dependent variable is financial performance proxied by Return on Assets (ROA) and Return on Equity (ROE). The study uses panel data analysis, whereby the annual reports of 16 Islamic banks in Malaysia were analysed over ten years from 2010 to 2019. Panel regression models consisting of random and fixed effects are incorporated for data evaluation. The study's findings show a significant influence of Shariah-compliant financing, Zakat, advertising and operational efficiency on financial performance represented by ROA. At the same time, the ROE model reports a significant influence of Zakat, advertising, non-performing financing and operational efficiency on the ROE of the banks. In addition, the effectiveness of the Shariah Committee moderates the influence of Shariah-compliant financing, Zakat, advertising, household financing and operational efficiency on the ROA of the banks. Further, the findings reveal that the Shariah Committee can moderate the influence of Zakat, advertising, non-performing financing and operational efficiency on the ROE of the banks. The study outcomes offer pivotal insights into effective Shariah committee roles in Malaysia, especially for the Shariah Advisory Council (SAC) of Bank Negara Malaysia (BNM) to implicitly optimise Islamic bank financial performance.